Spelling Errors Impede Recognition of Correctly Spelled Word Forms. (2nd January 2019) - Rahmanian, Sadaf; Kuperman, Victor
ABSTRACT: Spelling errors are typically thought of as an effect of a word's weak orthographic representation in an individual mind. What if existence of spelling errors is a partial cause of effortful orthographic learning and word recognition? We selected words that had homophonic substandard spelling variants of varying frequency (e.g., innocent and inocent occur in 69% and 31% of occurrences of the word, respectively). Conventional spellings were presented for recognition either in context (Experiment 1, eye-tracking sentence reading) or in isolation (Experiment 2, lexical decision). Words elicited longer fixation durations and lexical decision latencies if there was more uncertainty (higher entropy) regarding which spelling is a preferred one. The inhibitory effect of frequency was not modulated by spelling or other reading skill. This finding is in line with theories of learning that predict spelling errors to weaken associations between conventional spellings and the word's meaning.